ANALISIS YURIDIS PERJANJIAN BAKU DALAM KEHIDUPAN KONSUMEN - Ukas - - (Jurnal Cahaya Keadilan, 2018)
Standard contract they exist for adhering to social conditions and economic large companies, the company spring, or the utility hold cooperation for their interests. Standard contract contents be standardized made in the form a format raw. Reviewed in a juridical manner, standard contract was not minimum undang-undang, according to community needs and their activities acceptable, raw deal strength binding based on habits. Standard contract is an agreement which are written, the contents of are predetermined in advance by the party that in general have a position that are more dominant, and standards the contract that was originally follow the development of trade and or business transaction, good at home or abroad. The contract needs this standard becomes very important, raw contract which in this case when the contracts signed with a signature means other parties agree . Problem formula that is utilized first, To know indentured default in it consumen life not at cross of with private law and or could accepted . Second, factor-factor to become obstacle in the indentured default and if happen merchant transactions among producer with its consumer. To know Approximate methods that is utilized is jurisdictional normatif. Its data collecting tech library research that constitute main method.